Analisis Willingness to Pay untuk Peningkatan Pelayanan PDAM Tirta Bangka dengan menggunakan Contingent Valuation Method - Suldin Satriapriyaldi; Kancitra Pharmawati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PDAM Tirta Bangka had a poor service performance and health level in 2017, which showed that the existing service system was still underperforming. At the end of 2019, there were still customer complaints that showed customer dissatisfaction with the existing services. Therefore, an analysis was needed for the improvement of the Water Treatment Plant (WaTP) system. The research aims to analyse the willingness to pay (WTP) of Sungailiat and Pemali WaTP customers for the improvement of the drinking water supply system of PDAM Tirta Bangka. The method used was Contingent Valuation Method (CVM) through a questionnaire with bidding game technique. The number of respondents who were directly interviewed was 98 KK, divided into 24 KK in the service area of Sungailiat WaTP and 74 KK in the service area of Pemali WaTp. The average value of WTP obtained in the Sungailiat WaTP area was Rp. 175,250 and the total WTP was Rp. 24,600,442. Pemali Watp have an average Rp. 144.730 with total WTP was Rp. 43.816.757. Based on the results of multiple linear regression analysis; The WTP value at Sungailiat WaTP were influenced by watered bills, chlorine smell, and hours of drainage. Meanwhile, the factors influencing Pemali Watp were water bills and sediment.